HUBUNGAN INFORMASI TENTANG ALAT KONTRASEPSI DENGAN MOTIVASI PEMILIHAN ALAT KONTRASEPSI IMPLANT DI DESA POREH WILAYAH KERJA UPT. PUSKESMAS LENTENG KEC. LENTENG KAB. SUMENEP - Eva Nurhidayati; Dian Permatasari (Fakultas Ilmu Kesehatan, 2017)
The family planning program (KB), which has been running for 40 years, is able to preventa population increase of about 100 million people. BKKBN expects this year to increase theknowledge and skills of acceptor families. Namely about parenting and child development anddevelopment. In addition, improving the quality of elderly families, as well as the family's economicincome through the group of productive economic business activities. To know Information AboutRelationship With Contraceptive Implant Contraceptive Selection Motivation.The study design used is an analytical method with cross sectional design.The population inthis study as many as 633 large maternal EFA and EFA sample40 mothers. Engineering samplesare used random sampling. The data got fromthe village of the District Poreh Lanteng andquestionnaire data analysis while using the Spearman rank correlation test.The results showed the majority (62.5%) mothers receive less information, the majority(70.0%) mothers had a negative motivation in Contraceptive Implant Selection. Statisticalresearch results obtained using the Spearman rank correlation test Relationship WithInformation About Contraception Contraceptive Implant Selection Motivation in can sig ρ = 0.000<α = 0.05) so that H0 is rejected, which means there is the Relationship Between InformationAbout Motivation Election With Contraceptives Contraception.The conclusion of this study is the lack of information that pussy mother and motivationthat can negatively affect the Selection Tool contraceptives.